USM EMERGED AS CHAMPION AT THE DELL BUSINESS CHALLENGE 2017 - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, April 2017 – One of the two Universiti Sains Malaysia (USM) teams participated in the Dell Business Challenge 2017 has won the first prize. The team comprised of five students from the USM School of Management, namely Ng Yi Xiang, Shukri Muda, Tan Ke Xin, Sunisa Ai Som Chok and Izz Iyazi Razali, emerged as the champion in the challenge organised by Dell Malaysia recently, while the other team which comprised of Ng Boon Poh, Goh Suat Ting, Lee Cheng Sui, Moo Yi Zhi and Samantha Lim Siu Shi managed to secure second runnerup at the challenge.